Translating multimodal texts in space: A case study of St Mungo Museum of Religious Life and Art - Liao, Min-Hsiu (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Multimodality has received considerable critical attention in Translation Studies over the past decades. However, how translations interact with or within three-dimensional material space is still under-researched. This article proposes to use the study of geosemiotics (Scollon & Scollon, 2003) as the theoretical framework within which to explore this new territory. The case study was carried out at the St Mungo Museum of Religious Life and Art in Glasgow. The multimodal analysis divides museum space into four ranks: the museum surroundings, the museum building, the museum exhibition and the museum objects. The findings reveal that the translated exhibition texts interact with the four ranks of spaces to consistently minimize the narratives of Christian heritage in Glasgow and manifest a multi-religious and multi-ethnic Scottish identity. This study demonstrates how the (non-)provision of translations has the potential to influence the construction of in-place meaning in the multimodal museum space.